1998
DOI: 10.1029/98gl00640
|View full text |Cite
|
Sign up to set email alerts
|

MSX satellite observations of thunderstorm‐generated gravity waves in mid‐wave infrared images of the upper stratosphere

Abstract: Data from the Midcourse Space Experiment Tilere is evidence (R. H. Picard, J,'unes H. Brown (MSX) has provided the first observations of thunderstorm-personal communications, 1997) that gravity wave generated gravity waves imaged from space. Gravity wave structures are present in a number of MSX MWIR images. theory predicts that isolated, sufficiently convective This evidence is based on morphology, length scales, thunderstorms can launch waves mid create a unique power specUa and MWIR mdimive properties. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
153
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(162 citation statements)
references
References 4 publications
7
153
2
Order By: Relevance
“…Note that concentric rings from convective storms, like those in Fig. 6, have been occasionally observed in the OH airglow layer from deep convection (Taylor and Hapgood, 1988;Dewan et al, 1998;Sentman et al, 2003;Suzuki et al, 2007;Yue et al, 2009). …”
Section: Gravity Wave Excitation From Convective Plumesmentioning
confidence: 99%
“…Note that concentric rings from convective storms, like those in Fig. 6, have been occasionally observed in the OH airglow layer from deep convection (Taylor and Hapgood, 1988;Dewan et al, 1998;Sentman et al, 2003;Suzuki et al, 2007;Yue et al, 2009). …”
Section: Gravity Wave Excitation From Convective Plumesmentioning
confidence: 99%
“…Ionospheric studies have found evidence of D-layer heating due to thunderstorm quasi-electrostatic fields [Inan et al, 1996;Pasko et al, 1995], evidence of direct heating of the D-layer due to lightning electromagnetic pulses [Cheng and Cummer, 2005;Cheng et al, 2007], and evidence of atmospheric gravity wave (AGW) influence on the E-region ionosphere (100-150 km) [Davis and Johnson, 2005;Johnson and Davis, 2006]. Stratospheric AGW studies have shown neutral density fluctuations at altitudes of 60-90 km due to tropospheric thunderstorms activities [Taylor and Hapgood, 1988;Dewan et al, 1998;Sentman et al, 2003;Yue et al, 2009], and the electron density at this altitude is expected to fluctuate in a similar manner. However, because of low electron densities in the D-layer, it is difficult to continuously measure the electron density and its possible spatial and temporal fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Swenson and Mende, 1994;Taylor et al, 1995;Smith et al, 2000;Ejiri et al, 2003;Medeiros et al, 2003;Nielsen et al, 2006). Most of the time the waves appear near linear; however on occasions well-defined concentric rings of GWs are detected over or near severe thunderstorms (Taylor and Hapgood, 1988;Dewan et al, 1998;Sentman et al, 2003;Suzuki et al, 2007;Yue et al, 2008). Although Taylor and Hapgood (1988) inferred that a thunderstorm created the partial concentric rings which they observed, Sentman et al (2003) showed that the concentric rings they observed originated from a severe thunderstorm.…”
mentioning
confidence: 99%